The Energy Sector and the Internet of Things – Sustainable Consumption and Enhanced Security through Industrial Revolution 4.0 - Awang Dzul Hashriq Dharfizi (UUM Press, 2018)
With integration between machine automation and data being the hallmark of industrial revolution 4.0, the resilience of energy infrastructure in modern economy has taken a new significance. The study aims at discussing the potential and examining the impacts of the Internet of Things (IoT), which are smart devices with embedded sensors and connectivity, enabling data exchange to the energy sector. This technology contributes towards enhancing industry’s sustainable practices through the industrial internet of things. With data from the “edge of the grid,” these sensors assist in efficient energy consumption, providing constant monitoring for the regulatory authority, particularly on pollutant emissions. IoT technology may complement the national electric smart-grid, enhancing its reliability by feeding these raw data into machine learning neural network for the optimal operation. All these technologies shall complement one another, as Malaysia transform from a net energy exporter into an energy importer. Practicing efficient energy consumption can reduce this external dependency, and enhance national energy security. This paper derives statistical data sourced from the Energy Commission and technical data from publications of other scholars. On smaller scale, IoT implementation in manufacturing plants may resulted in 15% operating cost reduction. The benefits on national level implementation however remains unknown.